Students’ Ability in Writing Report Text of Grade XI at SMK Negeri 1 Painan - Rahmi Azizah (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This paper reports on the results of a study focusing on the analysis of students’ ability in writing report texts in terms of generic structure and language features. The subject of the research was the second year students at SMKN 1 Painan. To take the sample, stratified random sampling was used. The data of this research were the texts that were written by the students. Thus, to collect data, writing test was used. The test was analyzed by using scoring rubric. Based on the data analysis, it was found that there was no students had excellent and very good ability, 5 students had good ability, 14 students had fair ability. Then 7 students had poor ability and 4 students had very poor ability. The analysis of the data indicate the students’ ability in writing report text was fair. Also, most of students cannot achieve the passing grade which was 7. Hence, appropriate teaching techniques and approaches should be implemented.